Nachsorge bei Patientinnen mit Zervixkarzinom - Schulmeyer, Carla; Stuebs, Frederik A.; Beckmann, Matthias (Gynäkologe, 2020)
Follow-up of patients who underwent treatment for cervical cancer starts after completion of the primary treatment. It is important in aftercare to provide the patient with care both medically, in order to detect a recurrence as soon as possible and also as psychological guidance in order to record the effects of treatment, sexuality and relationship as well as the quality of life of the patient. It is also important to provide information about offers of assistance and psycho-oncological treatment options. The type of educational procedure and the approach for special collectives, such as patients after chemo(radio)therapy or after trachelectomy, are currently under discussion.
CRIS-Team Scopus Importer:2020-12-18
Keywords: Counselling; Diagnostic imaging; Human papillomaviruses; Quality of life; Sonography